Pengaruh Perceived Quality Terhadap Attitude Toward Brand Pada Pengguna Smartphone Samsung Di Surabaya - Jabin Franciosa Santoso (Jurnal Strategi Pemasaran, 2014)
In the current era of globalization, information and communcation technology growth rapidly with the discovery of a wide ramge of excellent prroducts in the field of information and communication. This has an impact on ease with which obtained by the community to interact with each other and obtain information. One of the discoveries leading products in the field of information and communcation is a smartphone. This Study will be conducted by distributing questionnaires of 100 respondents smartphone users. The sampling technique used was convenience sampling, data analysis technique used is the F test, t test, multiple linear regression analysis, and the coefficient of determination (R2). The result shows there is a significant and positive influence of the perceived quality of the attitude toward brand on the smartphone user is present on the variable peformance, the most dominant inffluence in attitude toward brand is peformance.